The Influence Of Work Motivation And Work Discipline On Employee Performance at Cv. Gunung Mas Putra Kencana Central Lampung - Hendri Dunan; Restu Windi Haryani (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to find out and analyze influence work motivation and work discipline on employee performance at CV. Gunung Mas Putra Kencana, Central Lampung. The population in this study were employees at CV. Gunung Mas Putra Kencana, totaling 45 employees. With relative population​ small, researchers use saturated sampling as a sampling technique, namely technique determination sample If all members of the population are taken as a sample, there are 45 respondents. This research uses quantitative research methods using primary data, namely a questionnaire that uses a scale likert. Data analysis using devices SPSS software to carry out data analysis, including multiple linear analysis, t test, F test, and coefficient of determination test. The research results show that both partially and anova, work motivation and work discipline have a significant effect on employee performance at CV. Gunung Mas Putra Kencana, Central Lampung.